Magia bruniana y socialismo utópico : el concepto de imaginación dialéctica de Alfonso Sastre en "dónde estás ulalume, dónde estás" - Diéguez, Mónica Poza (Acta Hispanica, 2010)
“In 1978 Alfonso Sastre (1926-) published his Crítica de la imagination, a capital work to understand his theory of drama, as Sastre defines and concretes the force of his writing on it. Imagination becomes a decisive element in Sastre’s works as he has stated in multiple interviews and in the present book as well –which is the first in a series of publications regarding the topic. In this article I analyze the concept of “dialectic imagination” as proposed by Alfonso Sastre in relation with that other concept of imaginatio developed by the hermetic tradition from Classical antiquity to Neoplatonism. More precisely, I will focus my analysis of ¿Dónde estás, Ulalume, dónde estás? (1990) to underline the connections between Sastre’s dialectic imagination and some interpretations regarding the works and thinking of Giordano Bruno.”